2009
DOI: 10.1002/hep.22879
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of occult hepatitis B virus strains in south african blood donors†

Abstract: T he implementation of nucleic acid testing (NAT) in blood donations from areas with high or low prevalence of hepatitis B virus (HBV) infection has resulted in the identification of a small number of infections in the preseroconversion window period (WP) 1 and a considerably larger number of blood units containing no detectable hepatitis B surface antigen (HBsAg) but low levels of HBV DNA associated, in most cases, with anti-HBc, suggesting an established infection. These cases were called occult HBV infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
68
4
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 24 publications
10
68
4
1
Order By: Relevance
“…In the case of Sudan, genotype E is dominant, but no genotype E OBI was identified. The average amino acid diversity within the MHR of the Sudanese genotype D OBIs was lower than the diversity reported in European genotype D and genotype A2 OBIs (9.8% versus 16 and 11%, respectively), but it was higher than that observed in South African genotype A1 (3%) and west African genotype E OBI strains (Ͻ1%) ( Table 2) (3,9,36).…”
Section: Vol 49 2011 Hbv Infection In Sudanese Blood Donors 303mentioning
confidence: 64%
See 1 more Smart Citation
“…In the case of Sudan, genotype E is dominant, but no genotype E OBI was identified. The average amino acid diversity within the MHR of the Sudanese genotype D OBIs was lower than the diversity reported in European genotype D and genotype A2 OBIs (9.8% versus 16 and 11%, respectively), but it was higher than that observed in South African genotype A1 (3%) and west African genotype E OBI strains (Ͻ1%) ( Table 2) (3,9,36).…”
Section: Vol 49 2011 Hbv Infection In Sudanese Blood Donors 303mentioning
confidence: 64%
“…All Sudanese OBI samples were anti-HBs positive, suggesting that these donors had recovered from past infection but were unable to fully control lowly replicating virus (9). The high anti-HBs prevalence in Sudanese OBIs differed from the ϳ50% prevalence reported for OBI donors from western Europe (HBV genotypes A2 and D) and South Africa (HBV genotype A1) and the 37.5% prevalence observed in OBIs genotype E from Ghana (3,9,36). Compared to HBsAgpositive samples, HBV genotype D was dominant in OBIs (five of six), and none was genotype E (Table 1).…”
Section: Vol 49 2011 Hbv Infection In Sudanese Blood Donors 303mentioning
confidence: 75%
“…Viral charge is generally low in literature in case of occult hepatitis B (less than 4 logs) [1] [22]. Sequencing of HBV was not carried out in our series, but Allain J P et al [23] found predominance of genotype A and genotype D.…”
Section: Viral Charge (Viral Dna)mentioning
confidence: 65%
“…Seromarker-negative SZ2 and SZ9 donors tested positive for HBV DNA by a Roche PCR-enzyme-linked immunosorbent assay (ELISA) and nested PCR in follow-up samples and were classified as seronegative or primary OBIs (1,15). Donor SZ25 with negative seromarkers was found reactive for both anti-HBs and anti-HBe 25 days after the index sample was obtained (postindex), and this sample was classified as OBI.…”
Section: Sample Classification and Characterizationmentioning
confidence: 99%
“…The mechanisms for generating OBI strains were mainly related to either imperfect immune control or to genetic viral defects and appeared largely genotype dependent (1,4). However, analysis of OBI strains of genotypes B and C prevalent in Southeast Asia and China has not been extensively explored, particularly in terms of molecular characterization (14,20).…”
mentioning
confidence: 99%